In vitro mycobacterial growth inhibition assays: A tool for the assessment of protective immunity and evaluation of tuberculosis vaccine efficacy. Issue 39 (7th September 2016) - Tanner, Rachel; O'Shea, Matthew K.; Fletcher, Helen A.; McShane, Helen
Abstract: Tuberculosis (TB) continues to pose a serious global health threat, and the current vaccine, BCG, has variable efficacy. However, the development of a more effective vaccine is severely hampered by the lack of an immune correlate of protection. Candidate vaccines are currently evaluated using preclinical animal models, but experiments are long and costly and it is unclear whether the outcomes are predictive of efficacy in humans. Unlike measurements of single immunological parameters, mycobacterial growth inhibition assays (MGIAs) represent an unbiased functional approach which takes into account a range of immune mechanisms and their complex interactions. Such a controlled system offers the potential to evaluate vaccine efficacy and study mediators of protective immunity against Mycobacterium tuberculosis ( M.tb ). This review discusses the underlying principles and relative merits and limitations of the different published MGIAs, their demonstrated abilities to measure mycobacterial growth inhibition and vaccine efficacy, and what has been learned about the immune mechanisms involved.